2022
DOI: 10.3390/ijms23169383
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Properties of Salecan–Soy Protein Isolate Composite Hydrogel Induced by Thermal Treatment and Transglutaminase

Abstract: Salecan (Sal) is a novel marine microbial polysaccharide. In the present research, Sal and soy protein isolate (SPI) were adopted to fabricate Sal–SPI composite hydrogel based on a stepwise process (thermal treatment and transglutaminase induction). The effect of Sal concentration on morphology, texture properties, and the microstructure of the hydrogel was evaluated. As Sal concentration varied from 0.4 to 0.6 wt%, hydrogel elasticity increased from 0.49 to 0.85 mm. Furthermore, the internal network structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…The determination of the percentage of salecan chains that were interconnected through citric acid esterification revealed high crosslinking degrees with values ranging from 91 to 96%. These high values suggest that salecan was almost completely crosslinked following the salecan crosslinking reaction and are in good agreement with other studies that mention salecan crosslinking in semi-interpenetrated structures [ 19 , 22 , 28 ]. It should be mentioned that one sample, S0, containing only salecan, was also prepared and subjected to the crosslinking process at a high temperature.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The determination of the percentage of salecan chains that were interconnected through citric acid esterification revealed high crosslinking degrees with values ranging from 91 to 96%. These high values suggest that salecan was almost completely crosslinked following the salecan crosslinking reaction and are in good agreement with other studies that mention salecan crosslinking in semi-interpenetrated structures [ 19 , 22 , 28 ]. It should be mentioned that one sample, S0, containing only salecan, was also prepared and subjected to the crosslinking process at a high temperature.…”
Section: Resultssupporting
confidence: 92%
“…FTIR spectra of salecan presented the characteristic absorption band of COH, stretching at 1018 cm –1 , which corresponds to the glucopyranose ring from the polysaccharide structure. Peaks at around 2900 cm −1 were attributed to the C-H stretching vibrations while the peaks from 3000–3600 cm −1 range belong to the OH stretching frequency [ 28 , 41 , 46 ]. Citric acid spectra displayed a split peak at ~1700 cm −1 , which corresponds to COOH from the C=O stretching vibration, peaks from 1200 cm −1 attributed to C-O-C bonds, along with peaks from 2800–3300 cm −1 region, which are associated with OH and CH stretching vibration, respectively [ 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gan et al [4] investigated the preparation of a composite hydrogel, cross-linked with hydrogen bonds, based on Salecan (Sal) and soy protein isolate (SPI). It was demonstrated that, by increasing the Sal concentration, the internal network structure of the composite hydrogel was denser and more uniform.…”
mentioning
confidence: 99%